Winchester Cathedral
Although so great an effort had been expended during the fourteenth century in improving the nave, the choir at Winchester had remained much as it had been left in 1360, after removal of the Norman apse had followed an Early English reconstruction of the eastern arm. The skills of chantry building can be seen in this magnificent reredos, erected by Bishop Fox behind the high altar. Although much defaced and mutilated during the Reformation, when all the statuary was removed, it has remained intact as a structure. At the top of the stone screen, which was erected between the piers, can be seen a classical frieze, evidence of the Renaissance to come. Above the screen are chests containing the bones of Saxon Kings and bishops, including those of King Canute and his queen, which have been in the cathedral from its earliest days.